2017
DOI: 10.5194/hess-21-4927-2017
|View full text |Cite
|
Sign up to set email alerts
|

State and parameter estimation of two land surface models using the ensemble Kalman filter and the particle filter

Abstract: Abstract. Land surface models (LSMs) use a large cohort of parameters and state variables to simulate the water and energy balance at the soil-atmosphere interface. Many of these model parameters cannot be measured directly in the field, and require calibration against measured fluxes of carbon dioxide, sensible and/or latent heat, and/or observations of the thermal and/or moisture state of the soil. Here, we evaluate the usefulness and applicability of four different data assimilation methods for joint parame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 79 publications
0
36
0
Order By: Relevance
“…The EnKF method of data assimilation is well-suited for non-linear mechanistic models like the GLM and enables ensemble-based forecasts of future states [ Dietze 2017a ]. Our implementation of the EnKF with state augmentation to calibrate parameters (Supporting Information A) follows Zhang et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…The EnKF method of data assimilation is well-suited for non-linear mechanistic models like the GLM and enables ensemble-based forecasts of future states [ Dietze 2017a ]. Our implementation of the EnKF with state augmentation to calibrate parameters (Supporting Information A) follows Zhang et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…Three different DA algorithms, including IEPFM, EnKF, and the differential evolution particle filter with MCMC (DEPFM), are applied in both experiments at the same time. It is noted that DEPFM follows the method of Vrugt et al to enhance sample diversity, because it outperforms the standard PF and demonstrates its effectiveness in many practical applications [15,24,25]. Comparing the performance of IEPFM with EnKF and DEPFM, it is found that IEPFM has the best data assimilation effect.…”
Section: Introductionmentioning
confidence: 94%
“…(i.e., by perturbing the model input, as well as the observations, to within their respective error ranges). For example, in Zhang et al (2017) where a joint stateparameter assimilation was undertaken using two land surface models, a value of zero for the model error was used since it was assumed that "uncertainty was captured by uncertain model parameters and model forcings." In this study, however, arbitrary model uncertainties, in the form of random global perturbations, were also assumed to represent the existing uncertainties in parameters, structure, and forcing data.…”
Section: Ossesmentioning
confidence: 99%
“…To account for these errors, data assimilation, which is defined as the integration of nearreal-time observations (likelihood) with the numerical model output data (prior) to give enhanced estimates (posterior) of the evolving system states (Swinbank & O'Neill, 1994), is carried out to update model state (and/or parameter) simulations. Majority of assimilation studies (e.g., Draper et al, 2011;Han et al, 2015;Montzka et al, 2011Montzka et al, 2012Moradkhani, 2008;Moradkhani, Hsu, et al, 2005;Zhang et al, 2017) have utilized measured and remotely sensed data within different assimilation frameworks. Among the assimilation algorithms, the particle filter has been found suitable for dealing with the highly nonlinear nature of soil water and heat flow models (Montzka et al, 2011;Moradkhani, Hsu, et al, 2005).…”
Section: Introductionmentioning
confidence: 99%